Promotion of CO2 capture performance using piperazine (PZ) and diethylenetriamine (DETA) bi‐solvent blends. Issue 2 (18th February 2019) - Liu, Ji; Li, Xiaoshan; Zhang, Zewu; Li, Liwei; Bi, Yajun; Zhang, Liqi
Abstract: The carbon dioxide post‐combustion capture process using amine solutions is considered the most appropriate method for CO2 capture from flue gas in power plants. This paper focuses on the CO2 capture performance of six common organic amines. Two amines, piperazine (PZ) and diethylenetriamine (DETA), which showed better performance, were then filtered out to form amine blends to improve performance further. The absorption heat from the CO2 absorbing process was measured directly using an advanced C80 micro calorimeter for more accurate calculation of regenerative energy consumption. Experimental results confirmed the optimal amine blend to be 10% PZ plus 20% DETA, with a 42% increase in absorption capacity and a 9% increase in initial absorption rate compared to traditional 30% monoethanolamine (MEA). The regeneration energy consumption of this chosen PZ‐DETA blend was calculated to be 3.979 GJ/ton CO2, a decrease of 9% compared with MEA. Moreover, it led to an improvement of about 55% in stable cyclic absorption capacity in comparison with 30% MEA. It was confirmed that this PZ‐DETA blend can bring practical economic benefits to industrial applications when replacing the current 30% MEA solution. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.